Semiconductor Nanocrystals as Light Harvesters in Solar Cells - Etgar, Lioz (Materials (Basel), 2013)
Photovoltaic cells use semiconductors to convert sunlight into electrical current and are regarded as a key technology for a sustainable energy supply. Quantum dot-based solar cells have shown great potential as next generation, high performance, low-cost photovoltaics due to the outstanding optoelectronic properties of quantum dots and their multiple exciton generation (MEG) capability. This review focuses on QDs as light harvesters in solar cells, including different structures of QD-based solar cells, such as QD heterojunction solar cells, QD-Schottky solar cells, QD-sensitized solar cells and the recent development in organic-inorganic perovskite heterojunction solar cells. Mechanisms, procedures, advantages, disadvantages and the latest results obtained in the field are described. To summarize, a future perspective is offered.